Profile of Culinary Vocational School Students' Learning Styles as a Basis for Choosing Science Learning Methods - Alimah, Siti Nur; Ulfah, Maria; Siswanto, Joko; Wahyu, Novanto Eka (Jurnal Mangifera Edu, 2023)
Based on the concept of student learning styles, students have strengths and weaknesses in learning. When the teacher applies learning methods that are not in accordance with their learning style, it will affect learning outcomes. The selection of the science learning method can be done by adjusting the student's learning style as a first step before carrying out the learning process. The purpose of this research is to identify profiles of students' learning styles in order to be able to choose appropriate learning methods. This research is a qualitative descriptive study, using a purposive sampling technique. The research subjects consisted of 32 students of class X Culinary 2 at SMK Negeri 6 Semarang. The learning styles studied focus on visual, auditory, and kinesthetic learning styles. Data collection techniques using questionnaires to identify student learning styles and observation. The data obtained were analyzed qualitatively. The results obtained are that students are more inclined to the visual learning style by 47%, while the auditory is 16.2% and the kinesthetic is 36.8%. So it can be concluded that students in the class have diverse learning styles. Teachers cannot emphasize only one learning style so that the learning methods applied must be varied and adapted to the learning styles possessed by students.